RANCANG BANGUN BLUELIGHT THERAPHY PADA INFANT WARMER BERBASIS MIKROKONTROLER ATMega8535 - Ilhamzah Pahutar; Dzia Ur Ridha (JURNAL MUTIARA ELEKTROMEDIK, 2019)
Phototherapy is a therapy using blue light (bluelight) to provide therapy to babies affected by jaundice, besides as a therapeutic tool the design of this tool incorporates an infant warmer system that functions to warm newborns in low temperature conditions, then designed an Infant Warmer device equipped Phototherapy The tool is also equipped with temperature monitoring which serves to monitor the baby's body temperature when doing phototherapy. The design of this tool uses an ATMega16 microcontroller and is equipped with a temperature sensor. The working principle of this tool when the phototherapy system switch is activated it will display the time setting and temperature monitoring display.Based on the temperature data retrieval with the settings 34C, 35C and 37C, the results do not reach the set temperature. Bluelight therapy can work properly, but the results of the therapeutic rays do not reach the standard on the actual tool